The construction of access: the eugenic precedent of the Americans with Disabilities Act. Issue 3 (4th May 2017) - Wheeler, Stephanie K.
Abstract: This paper interrogates the language of the legal precedents of the Americans with Disabilities Act (ADA) and their function, including the 1891 Immigration Law and the series of 'ugly laws' that spanned from the late nineteenth century until the early twentieth century. Legislative language is used to construct and deploy static definitions of normalcy and disability, relying on 'objective' evidence couched in medical and scientific discourse. The purpose of this paper is to uncover the legislative precedents of the Americans with Disabilities Act Amendments Act (ADAAA) that were motivated by the eugenicist imperative to strengthen the image of a productive and robust nation. I begin by outlining eugenicist logic and demonstrate how it functions within a semiotic system. Then, I will introduce the process by which eugenicist logic works within legal semiotics. Lastly, I will provide three examples of how this process functions in the legislative language and implementation of the 1891 Immigration Act, the 'ugly laws' and the ADAAA. Ultimately, I will demonstrate how all three provide evidence of a pattern of semiotic systems that pathologize human difference and manages these differences so as to segregate and disenfranchise in the name of nationalism.